RP-HPLC Estimation of Nelfinavir Mesylate in Bulk Drug and Pharmaceutical Formulation - S. SARSAMBI*, PRAKASH; GOWRISANKAR†, D. (Asian Journal of Chemistry, 2024)
A simple, rapid and reproducible high performance reversed phase liquid chromatographic method has been developed for the estimation of nelfinavir in bulk drug sample and pharmaceutical dosage forms using kromosil C18 column. The mobile phase consists of potassium dihydrogen phosphate and acetonitrile in the ratio of 30:70 v/v, respectively and was pumped at rate of 1.3 mL/min at 25 °C. The detection was carried out at 220 nm and the calibration curve was linear in the range of 5 to 30 μg/mL. The method was statistically validated for its linearity, precision and accuracy. The intra-day and inter-day variation was found to be less than 1 % showing high precision of the assay method. Due to its simplicity, rapidness, high precision and accuracy, the proposed RP-HPLC method may be used for determining nelfinavir mesylate in bulk drug sample or in pharmaceutical formulations.